The Role of Educational Level in Enhancing Marital Satisfaction within Islamic Family Law: Implications for Achieving SDGs 4 (2030) - Edy Usman (Lembaga Bale Literasi, 2025)
This study aims to analyze the role of educational level in enhancing marital satisfaction within the framework of Islamic family law and to examine its implications for the achievement of Sustainable Development Goals (SDGs), particularly Goal 4 on quality education. The research employs a qualitative approach with a case study design, involving six informants selected purposively based on variations in educational background and social context. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The validity of the data was ensured through triangulation of sources and techniques. The findings reveal that educational level plays a significant role in improving marital satisfaction through several key mechanisms, including the enhancement of interpersonal communication, adaptive conflict resolution, comprehensive understanding of spousal rights and obligations in Islamic family law, and the development of emotional and rational maturity. However, the influence of education is not absolute, as it is mediated by religiosity, socio-cultural factors, and disparities in educational background between spouses. The study also highlights that the integration of formal education with Islamic values is essential in fostering harmonious, balanced, and sustainable marital relationships. Furthermore, the study demonstrates that quality education contributes not only to individual academic achievement but also to the strengthening of family institutions, which are fundamental to social resilience. These findings imply that education serves as a strategic instrument in achieving SDGs 4 by promoting not only access and participation but also the quality and social impact of education. Therefore, an integrative and value-based educational approach is necessary to support sustainable family and societal development.